Samtidsteologiens fokus og horisont - Gregersen, Niels Henrik (Dansk Teologisk Tidsskrift, 2011)
In this response to Asle Eikrem’s discussion of my program for “Systematic Theology as Contemporary Theology” (DTT 2008, 290-310), I lay out my principled reasons for maintaining the distinction between Theology1, 2 and 3. While I find Eikrem’s proposals concerning the relation between the semantics and the pragmatics in Theology1 revealing, I argue that systematic theology should not be understood as a purely theoretical metaphysics.